Design and Development of a Multimedia Website for Guiding the Use of the My Icon Plus Application - Rifky Fransdita Sebayang; Supiyandi (Bahasa Indonesia, 2026)
The development of information technology has increased the use of digital applications in various services, including the My Icon Plus application. However, many users still face difficulties in understanding how to use the available features due to the lack of effective guidance media. This study aims to design and develop a multimedia website as a user guide for the My Icon Plus application to make it easier for users to understand. The method used is Research and Development (R&D) with stages including needs analysis, system design, implementation, testing, and evaluation. The website is developed using HTML, PHP, and MySQL technologies and is equipped with multimedia content such as images and step-by-step instructions. The results show that the developed website is able to present information in a more interactive, structured, and accessible way, helping users understand login processes, issue reporting, and payment methods. Therefore, this website is expected to improve usability and enhance the overall user experience.